Multiple solutions to the planar plateau problem - Schneider, Matthias (Differential and integral equations, 2012)
We give existence and non-uniqueness results for simple planar curves with prescribed geodesic curvature.
Last revised 26 Apr 2010
DOI nicht vorhanden
Gesehen am 28.06.2018